Priya puts herself first - Fairbairn, Nathan; Msassyk (2023)
Priya Gupta and her friends Gabby Jordan and Mindy Park are the best dog-walkers in town and, although they each face challenges during the holidays, their friendship get them through it all.
Keywords: Graphic novels; Friendship -- Fiction; Dog walking -- Fiction; Dogs -- Fiction